Inhibition of Matrix Metalloproteinases and Cancer Cell Detachment by Ru(II) Polypyridyl Complexes Containing 4,7-Diphenyl-1,10-phenanthroline Ligands-New Candidates for Antimetastatic Agents - Przemysław Gajda-Morszewski; Ilona Gurgul; Ewelina Janczy-Cempa; Olga Mazuryk; Michał Łomzik; Małgorzata Brindell (MDPI AG, 2021)
Primary tumor targeting is the dominant approach in drug development, while metastasis is the leading cause of cancer death. Therefore, in addition to the cytotoxic activity of a series of Ru(II) polypyridyl complexes of the type [Ru(dip)2L]2+ (dip: 4,7-diphenyl-1,10-phenanthroline while L = dip; bpy: 2,2'-bipyridine; bpy-SC: bipyridine derivative bearing a semicarbazone 2-formylopyridine moiety; dpq, dpq(CH3)2, dpb: quinoxaline derivatives) their ability to inhibit cell detachment was investigated. In vitro studies performed on lung cancer A549 cells showed that they accumulate in cells very well and exhibit moderate cytotoxicity with IC50 ranging from 4 to 13 µM. Three of the studied compounds that have dip, bpy-SC, or dpb ligands after treatment of the cells with a non-toxic dose (<1/2IC50) enhanced their adhesion properties demonstrated by lower detachment in the trypsin resistance assay. The same complexes inhibited both MMP-2 and MMP-9 enzyme activities with IC50 ranging from 2 to 12 µM; however, the MMP-9 inhibition was stronger. More detailed studies for [Ru(dip)2(bpy-SC)]2+, which induced the greatest increase in cell adhesion, revealed that it is predominately accumulated in the cytoskeletal fraction of A549 cells. Moreover, cells treated with this compound showed the localization of MMP-9 to a greater extent also in the cytoskeleton. Taken together, our results indicate the possibility of a reduction of metastatic cells escaping from the primary lesion to the surrounding tissue by prevention of their detachment and by influencing the activity of MMP-2 and MMP-9.